Molecular Diversity of Mold Associated with Gatotan - Steffanus Pranoto Hallis; Anastasia Tatik Hartanti; Agustin Wydia Gunawan (Indonesian Society for microbiology, 2021)
Gatotan is a raw material to make gatot, an Indonesian fermented food, especially in Central Java, made from cassava tubers. Traditionally, the cassava tubers are sun-dried for several days until the black color appears. However, natural fermentation allowed by many types of microorganisms, especially mold in this process could raise concerns about the food safety issues. Previously, the identifications of molds in gatotan were based on morphological observation. Here, we reported the diversity of molds associated with gatotan using molecular identification method. The molecular identification was based on ribosomal DNA internal transcribed spacer (ITS) amplification sequences using combination of ITS4 and ITS5 primers. A total of ten molds were isolated and phylogenetic trees were constructed based on ribosomal DNA sequences. Our results showed that the molds were classified into Lasiodiplodia spp., Trichoderma sp., Aspergillus nomius, Fusarium oxysporum, and Cladosporium sphaerospermum.